Is Genericness Still Adequately Defined? Internet Search Firms and the Economic Rationale for Trademarks. (May 2023) - Shackell, Cameron
Landes and Posner's highly cited economics of trademark law based on search cost reduction has influenced economists, legislators, and courts for decades. Their account, however, predates consumer use of the Internet for search and did not anticipate the rise of firms such as Google to economy-wide power in search. Consequently, trademark law intended to help consumers find a preferred brand now also protects the means they typically use. An outdated view of trademarks as a natural and equitable right––very scrutable to STS––has led to Internet search firms owning reflexive "marks for finding other marks, " a structural advantage they have exploited through new dynamic and microtargeted forms of advertising into technoscientific rentiership. This paper revises Landes and Posner's model to fit the case of an economy containing dominant firms with significant economy-wide search cost reduction power, adding (1) differentiation of technological elements of the original formal model and (2) analysis of the distribution and function of marks such as GOOGLE in consumer decision-making. The updated theory shows that marks granted to search firms are equivalent to generic marks in economic effect and constitute a new but unrecognized class that are functionally "super-generic."